Real-Time data Integration dan Modeling Untuk Kebutuhan Business Intelligence Menggunakan Pendekatan Agile - Rudi, Rudi Hartono (Institut Teknologi Garut, 2025)
The purpose of this research is to explore how real-time data integration and adaptive modeling can support faster and more accurate data-driven decision making in a dynamic business environment. The Agile BI method allows organizations or companies to respond quickly to changing business needs through flexible iterative cycles. The results of this research show that the use of the Agile BI approach in real-time data integration can be developed by producing visual dashboard products for business analysis and decision-making needs. This research also provides practical advice related to strengthening technological infrastructure, increasing the capacity of human resources, and managing data security to support the implementation of Agile BI optimally.